Mental toughness and social loafing in male elite ice hockey players in Norway - Høigaard, R.; Rodahl, S.; Peters, D. M. (World Congress of Performance Analysis of Sport IX, 2012)
Social loafing (SL) refers to an individuals` tendency to exert less effort when working with others than when working alone, which may result in team performance that is not optimal. The presence of SL at elite level have been documented (Høigaard 2010) and several situational factors e.g. identifiability of individual effort, team cohesion, motivational climate, appear to moderate the magnitude SL with research recommending the investigation of personal factors in relation to SL (Høigaard et al. 2010). One such personal factor is Mental Toughness (MT) which is considered to be a crucial attribute in competitive sport and is defined by Loehr (1994, p.5) as `the ability to consistently perform toward the upper range of your talent and skills regardless of competitive circumstances`. Theoretically therefore it is reasonable to investigate if MT is negatively related to SL among high performance athletes. One hundred and fifty five players from 11 teams in the Norwegian premier league (mean age 22.7± 4.0 years; mean time playing at elite level 4.3±3.8 years) completed the Self-Reported Social Loafing Questionnaire (SRSLQ, Høigaard et al. 2010) and the Sport Mental Toughness Questionnaire (SMTQ; Sheard et al. 2009). The higher the SRSLQ score the higher the degree of SL and the higher the score on three SMTQ MT components; Confidence, Constancy and Control the higher the level of MT. As can be seen in Table 1, SL was low; perceived level of MT was relatively high & that MT is negatively related to SL (Table 1). The results confirm that MT is invaluable aspect of elite athletes. Furthermore it also indicates that MT in addition to influence athletes` mental attitude also is related to motivation and effort. Taken together, this is all important factors in on order to improve team effectiveness and team performance. Investigate antecedents to MT is therefore of vital importance, and specifically what and how athletes and coaches can develop MT.